Digital marketing in theatre organizations: A study on Mahua fun age troupe in China / Wang Peng - Wang , Peng (2020)
The rapid popularization of Internet technology has changed the face of the whole world. With the advent of the era of digital, online marketing has come in a new way. Based on the traditional marketing methods, the marketing concept and model evolved from the traditional marketing methods are constantly innovated to play a role in the enterprise's marketing strategy and promote the enterprise to complete the overall business objectives more quickly. Shuyu Qi, a professor at the China academy of administration, said that in today's world, cultural development and economic development are increasingly integrated, and cultural industry has gradually become an important driving force for economic growth. Many countries have increased their efforts in the development of cultural industry, and the development of cultural industry in the world presents a situation of fierce competition (Daily, 2013). Vigorously developing the cultural industry has become a new trend in China. The successful operation of the theater will bring huge benefits to the whole cultural performance and urban development. In China today's drama performance market, young and middle-aged audience groups gradually become the main consumer, especially in China's biggest cities, drama lovers' consumption enthusiasm for drama performance is very high, in recent years, a number of emerging drama groups in China's rise, many works have a high box office income. The drama consumer group will become one of the main forces of social consumption in China. In the Internet era, how to adopt marketing strategies for drama lovers is a question that every theater operator must think about. This paper adopts the qualitative mode of on focusing on research methods like interview, observation and narrative method. The researcher through the case analysis of Mahua Fun Age company in China, analyzes the digital marketing of target audience in the current market of theatre performance market in China. To explore the development trend, marketing environment and the strategy of marketing of theatre performance market in the digital marketing era. Finally, based on the research conclusions, the author puts forward relevant and feasible digital marketing strategies suggestions, and reflects on the deficiencies of this research.